2017
DOI: 10.1177/0307174x1704400207
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Composites and Polymer Materials Science

Abstract: The current situation regarding the production, investigation, and processing of polymer-matrix-based nanocomposite materials is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 24 publications
0
9
0
3
Order By: Relevance
“…To clarify processes connected with the improvement of the electret properties of the polymer materials, it is necessary, first of all, to have sufficiently convincing data on the structure and properties of the filled composite materials. In particular, in the work [44,45] the general state of the problem of preparation and investigation of the composite materials on the basis of polyolefins and mineral fillers is considered. The main perspective directions of preparation, processing and application of the composite materials were shown.…”
Section: Physico-mechanical Properties Of Composite Materials Based Omentioning
confidence: 99%
See 1 more Smart Citation
“…To clarify processes connected with the improvement of the electret properties of the polymer materials, it is necessary, first of all, to have sufficiently convincing data on the structure and properties of the filled composite materials. In particular, in the work [44,45] the general state of the problem of preparation and investigation of the composite materials on the basis of polyolefins and mineral fillers is considered. The main perspective directions of preparation, processing and application of the composite materials were shown.…”
Section: Physico-mechanical Properties Of Composite Materials Based Omentioning
confidence: 99%
“…In the works [46][47][48][49][50], the results of investigation of influence of the standard mineral fillers on basic physical-mechanical and physical-chemical properties of nanocomposites on the basis of comparatively new types of thermoplastic polyolefins -statistic copolymer of ethylene with propylene (REP) and block copolymer of propylene with ethylene (BEP) were presented. It revealed that an introduction of multifunctional structure-forming agentsalizarin and zinc stearate within the ranges of 1.0% mass in the composition of above-mentioned polyolefins improves essentially the strength and rheological characteristics of the composite materials on their basis.…”
Section: Physico-mechanical Properties Of Composite Materials Based Omentioning
confidence: 99%
“…One of the reasons for increase in the relaxing, initial, and quasi-equilibrium stresses of nanocomposites by comparison with unfilled PE, and also a reason for increase in the rigidity of the composites, may be the increase in the degree of crystallinity of the PE when it is filled with nanoparticles. Filler particles may serve as crystallisation nuclei, the presence of which can lead to an increase in the degree of crystallinity of the nanocomposites [8].…”
Section: The Relaxation Properties Of Nanocompositesmentioning
confidence: 99%
“…These strands were then subjected to air cooling with subsequent pelletisation on a laboratory blade pelletiser. A similar two-stage scheme had been used to achieve the most uniform distribution of nanoadditives in HDPE, which during processing are prone to form aggregates that prevent their uniform distribution in the matrix and thereby do not make it possible to achieve the desired effectiveness during filling of the polymer [8].…”
Section: T/48mentioning
confidence: 99%